NLRP3: Role in ischemia/reperfusion injuries - Ghafouri-Fard, Soudeh; Shoorei, Hamed; Poornajaf, Yadollah; Hussen, Bashdar Mahmud; Hajiesmaeili, Yasaman; Abak, Atefe; Taheri, Mohammad; Eghbali, Ahmad (Frontiers in Immunology, 2022)
NLR family pyrin domain containing 3 (NLRP3) is expressed in immune cells, especially in dendritic cells and macrophages and acts as a constituent of the inflammasome. This protein acts as a pattern recognition receptor identifying pathogen-associated molecular patterns. In addition to recognition of pathogen-associated molecular patterns, it recognizes damage-associated molecular patterns. Triggering of NLRP3 inflammasome by molecules ATP released from injured cells results in the activation of the inflammatory cytokines IL-1β and IL-18. Abnormal activation of NLRP3 inflammasome has been demonstrated to stimulate inflammatory or metabolic diseases. Thus, NLRP3 is regarded as a proper target for decreasing activity of NLRP3 inflammasome. Recent studies have also shown abnormal activity of NLRP3 in ischemia/reperfusion (I/R) injuries. In the current review, we have focused on the role of this protein in I/R injuries in the gastrointestinal, neurovascular and cardiovascular systems.